Comparison of Neutrophil-Lymphocyte Ratio between Diabetic Nephropathy and Without Diabetic Nephropathy in Type 2 Diabetes Mellitus at a Tertiary Care Centre - Yadav, Anil; Jyoti, Sabita; Yadav, Pratima; Rai, Rabin; Mehta, Ram Kumar; Parajuli, Surya Bahadur; Yadav, Indra (Journal of Nepalgunj Medical College, 2023)
Introduction: Type 2 Diabetes mellitus is a kind of systemic disease with serious microvascular and macrovascular complications incorporate diabetic nephropathy. The Neutrophil lymphocyte ratio (NLR) is a simple and cheap laboratory tool used to predict the prognosis of many non-communicable diseases such as diabetic nephropathy. Aims: To compare neutrophil-lymphocyte ratio between type 2 diabetes mellitus with diabetic nephropathy and without diabetic nephropathy. Methods: An observational cross-sectional study was conducted at teaching hospital, Morang, Nepal. Non probability convenience sampling technique was used to collect data of 226 participants by using clinical and laboratory forms and formats. The data was analysed in SPSS version 21.00. Results: Laboratory parameters were compared between two groups. High density lipoprotein (p=0.028) and low density lipoprotein (p<0.01) and glycaemic parameters fasting blood glucose (p=0.028), postprandial blood glucose (p=0.0005) and glycated haemoglobin (p=0.007) were found to be significantly raised in diabetic nephropathy patients as compared to without diabetic nephropathy patient. Renal function tests such as estimated glomerular filtration rate (p<0.01), serum creatinine (p<0.01), urine albumin-to-creatinine ratio (p< 0.01) showed high significant differences between two groups. Blood cell count, platelets (p<0.01) and white blood cell (p<0.01) were found to have statistically significant between patients with diabetic nephropathy and without diabetic nephropathy. Majority of individuals with smoking habit fell in diabetic nephropathy group as compared with individual without diabetic nephropathy. Neutrophil lymphocyte ratio was high in diabetic nephropathy group. Conclusion: The neutrophil-lymphocyte ratio was significantly raised in type 2 diabetic patients with diabetic nephropathy. Based on above finding, neutrophil-lymphocyte ratio may be considered as a predictor and a prognostic biomarker of diabetic nephropathy.